Участь львівської архітектурної школи в заходах Празького Квадрієнале 2019 року - Проскуряков, В. І.; Proskuryakov, V. I. (Видавництво Львівської політехніки, 2019)
Висвітлено участь викладачів і студентів підрозділу Львіської архітектурної школи – кафедри дизайну архітектурного середовища Національного університету “Львівська політехніка” – в заходах всесвітньої виставки Празьке Квадрієнале 19, що відбувалася в столиці Чехії від 6 до 16 червня 2019 року.

The article covers the participation of teachers and students of the department of the Lviv Architectural School – the Department of Architectural Design of the National University of Lviv Polytechnic in the events of the Prague Prague Quadrienale 19, held in the Czech capital from June 6 to 16, 2019. The main activities in which the Department of Architectural Design took part were as follows: Teachers and students of the department designed, manufactured and assembled in the spaces of the main exhibition pavilion PQ19 – Industrial Palace – the first pavilion for the First Ukrainian National Theater Exhibition. Six teachers of the department, led by its head, have prepared and reported their scientific reconnaissance in collaboration with participants from Canada and Georgia at the Fourth Transatlantic Seminar on Theater Arts. The head of the department spoke at the highest level of the conference PQ19 Talks – history, theory, cooperation with the report “Features of cooperation of architects and theater designers” (According to the results of the student Ukrainian-Canadian design seminar in Lviv in 2017 theater and entertainment and cultural and educational functions. Also, an important event of the department was the restoration, delivery and installation in Prague of the Quadriennial in the Lapidarium Palace of a model of the brilliant artist E. Lisik to the ballet play “Creation of the World”
Participation of lviv architectural school in the events of the Prague Quadrienal 2019
Keywords: виставки країн і регіонів; студентські; музейні; специфічні виставки дизайну і простору; доповнені елементами проектування в заходах Празького Квадрієнале; Exhibitions of countries and regions; student; museum; specific exhibitions of design andspace; reports; seminars; design in the events of the Prague Quadrienale